2017
DOI: 10.1002/jhet.3058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Pyrido[2,3‐d]pyrimidine and Pyrido[3,2‐e][1,3,4]triazolo and Tetrazolo[1,5‐c]pyrimidine Derivatives as Potential Antimicrobial and Anticancer Agents

Abstract: A novel series of pyrido[2,3‐d]pyrimidines 3a–d, 4a–d, 5a–d, 6a–d, and 7a–d; pyrido[3,2‐e][1,3,4]triazolo; and tetrazolo[1,5‐c]pyrimidines 10a–d and 11a–d was synthesized through different chemical reactions starting from 2‐amino‐3‐cyano‐4,6‐diarylpyridines. The newly synthesized heterocycles were characterized by elemental analysis, IR, 1H‐NMR, 13C‐NMR, and mass spectral data. Compounds have been screened for their antibacterial and antifungal activities. The data showed that the presence of electron‐donating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In a parallel study HepG-2 and HCT-116 cancer cell lines were screened by novel pyrido[2,3-d]pyrimidine derivatives and 80(a-d) were found to be most active (Fig. 26) [83]. Pyrido [2,3- 3-a]pyrimidine derivatives and pyrido [2,3-d]pyrimidines were evaluated against two cancer cell lines, namely PC-3 and A-549.…”
Section: Pyrido[23-d]pyrimidine Derivativesmentioning
confidence: 99%
“…In a parallel study HepG-2 and HCT-116 cancer cell lines were screened by novel pyrido[2,3-d]pyrimidine derivatives and 80(a-d) were found to be most active (Fig. 26) [83]. Pyrido [2,3- 3-a]pyrimidine derivatives and pyrido [2,3-d]pyrimidines were evaluated against two cancer cell lines, namely PC-3 and A-549.…”
Section: Pyrido[23-d]pyrimidine Derivativesmentioning
confidence: 99%
“…Continuing our interest in preparing of new heterocyclic compounds and examining their various biological activities [ 1 6 ], this work was designed to prepare new derivatives of condensed and non-condensed five-membered rings with pyrimidine. Pyrimidine derivatives have aroused the interest of researchers in recent years, as they have demonstrated a wide variety of biological activities such as antibacterial [ 6 ], antiallergic, antihypertensive [ 7 ] and antitumor activity [ 5 , 8 ], along with their cardiopulmonary and bronchodilating effect [ 9 ]. It has been observed that the substitution of the benzene ring in pyrimidine derivatives with heterocyclic moieties such as pyrrole and thiophene shows some biological activities such as anti-proliferative and anti-inflammatory activities [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, pyrido [2,3-d]pyrimidines derivatives are extremely important for their biological activities. For example, some are antitumor [51,52], antibacterial [52], anticonvulsant [53], antipyretic [54], analgesic, and CNS depressant activity [55]. Thus, heating compound 1a with 2-(4-methoxybenzylidene) malononitrile in ethanol under refluxing in the presence of a catalytic amount of ammonium acetate leads to the formation of 7-aminopyrido [2, 3-d] pyrimidine carbonitrile derivative 9.…”
Section: Chemistrymentioning
confidence: 99%